Ischemic preconditioning enhances energy supply during frequency speed kick test in Taekwondo athletes: A randomized crossover study - Ou, Z.; Yang, L.; Xie, D.; Zhu, H.; Weng, X.; Xu, G. (PLOS ONE, 2026)
Purpose This study aimed to examine the effect of ischemic preconditioning (IPC) on energy supply during sport-specific tests in male taekwondo athletes. To our knowledge, this is the first investigation of IPC`s efficacy in enhancing energy supply in a taekwondo context, underscoring its potential to optimize performance in combat sports.